System Integration for Plastic Electronics Using Room‐Temperature Ultrasonic Welding. Issue 5 (28th February 2020) - Dou, Guangbin; Holmes, Andrew S.
Abstract : Plastic electronics is attracting increasing attention for both high‐end applications such as flexible organic light‐emitting diode (OLED) displays in mobile phones and low‐cost items such as plastic radio frequency identification (RFID) tags for product labeling and tracking. However, there are numerous technological challenges, not least of which is to develop robust and reliable packaging methods. Unfortunately, most of the established packaging technologies used in conventional silicon electronics are not transferable to plastic electronics due to the high process temperatures involved. The use of room‐temperature ultrasonic welding for the realization of multilayer plastic electronic circuits is explored, identifying two distinct modes of ultrasonic welding that can form combined electrical and mechanical connections between adjacent low‐temperature polymer films with either aluminum or printed silver metallization. Fully functional multilayer wireless charging coils and RFID tags are fabricated to demonstrate the potential of this new system integration approach. Abstract : A room‐temperature ultrasonic welding process for plastic electronics is demonstrated. The process allows robust interlayer mechanical and electrical connections to be formed between the layers in a multilayer stack of metalized low‐temperature polymer films. This technical innovation provides a system integration approach for complex hybrid plastic electronic systems, incorporating both flexible components and conventional silicon devices.